The need for a holistic approach for SSc-ILD: achievements and ambiguity in a devastating disease - Hoffmann-Vold, Anna-Maria; Kreuter, Michael (Respiratory research, 2020)
Systemic sclerosis (SSc) is a multi-organ autoimmune disease with complex interactions between immune-mediated inflammatory processes and vascular pathology leading to small vessel obliteration, promoting uncontrolled fibrosis of skin and internal organs. Interstitial lung disease (ILD) is a common but highly variable manifestation of SSc and is associated with high morbidity and mortality. Treatment approaches have focused on immunosuppressive therapies, which have shown some efficacy on lung function. Recently, a large phase 3 trial showed that treatment with nintedanib was associated with a reduction in lung function decline. None of the conducted randomized clinical trials have so far shown convincing efficacy on other outcome measures including quality of life determined by patient reported outcomes. Little evidence is available for non-pharmacological treatment and supportive care specifically for SSc-ILD patients, including pulmonary rehabilitation, supplemental oxygen, symptom relief and adequate information. Improved management of SSc-ILD patients based on a holistic approach is necessary to support patients in maintaining as much quality of life as possible throughout the disease course and to improve long-term outcomes.
Gesehen am 26.10.2020